The Quality of Competitive Information and Its Role in Achieving Organizational Excellence in the Palestinian Renewable-energy Companies - M. Meshmesh, Ashraf; M. Hassouna , Yasser (Jordan Journal of Business Administration, 2023)
This study aims to show the role of the competitive-information quality in the Palestinian renewable-energy companies in achieving organizational excellence. This study used a questionnaire as a tool to collect information from the study sample which consists of 123 employees working at the Palestinian renewable-energy companies in the Gaza Strip. This study uses the comprehensive survey, putting all members of the study population as a sample under analysis. Moreover, the researchers relied on the descriptive analytical approach. The study reached that the content criterion is a higher criterion for the quality of competitive information in affecting organizational excellence than the temporal and formal criteria. The results reflected that the study population’s perspective is that all of the competitive-information quality criteria are widely available at the Palestinian renewable-energy companies. The results also showed that the study population highly approved that the companies are seeking organizational excellence. The study recommended to find an information team within the Palestinian renewable-energy companies specialized in evaluating solar systems according to the criteria of competitive-information quality and its three dimensions (temporal, content and formal criteria). In other words, the higher the degrees of the criteria of quality of the competitive information, the higher the organizational excellence and vice versa.